2002
DOI: 10.1074/jbc.m201774200
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Hydrolysis of Pyridoxine-5′-β-d-glucoside Is Catalyzed by Intestinal Lactase-Phlorizin Hydrolase

Abstract: An obligatory step in the mammalian nutritional utilization of pyridoxine-5-␤-D-glucoside (PNG) is the intestinal hydrolysis of its ␤-glucosidic bond that releases pyridoxine (PN). This laboratory previously reported the purification and partial characterization of a novel cytosolic enzyme, designated PNG hydrolase, which hydrolyzed PNG. An investigation of the subcellular distribution of intestinal PNG hydrolysis found substantial hydrolytic activity in the total membrane fraction, of which 40 -50% was locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Pyridoxine-5 0 -b-D-glucoside (PNG) (Section 2.1) is hydrolysed enzymatically by the PNG hydrolase (Nakano et al, 1997) and the brush border lactase-phlorizin hydrolase (Mackey et al, 2002) before its absorption in the small intestine. However, PNG can also be absorbed unchanged (IOM, 1998).…”
Section: Intestinal Absorption and Bioavailabilitymentioning
confidence: 99%
“…Pyridoxine-5 0 -b-D-glucoside (PNG) (Section 2.1) is hydrolysed enzymatically by the PNG hydrolase (Nakano et al, 1997) and the brush border lactase-phlorizin hydrolase (Mackey et al, 2002) before its absorption in the small intestine. However, PNG can also be absorbed unchanged (IOM, 1998).…”
Section: Intestinal Absorption and Bioavailabilitymentioning
confidence: 99%
“…Lactase (lactase phlorizinhydrolase-LPH, EC 3.2.1.62/108; note b galactosidase is EC 3.2.1.23, mistakenly used for lactase in some publications) is highly unusual, having two active sites within one polypeptide chain, one hydrolysing lactose, the other aryl and aliphatic glycosides such as phlorizin into glucose and phloretin, the latter being a potent diabetic agent. Two important natural substrates for this latter site are cerebrosides, a crucial source of sphingosine, and glycosyl-pyridoxal, 27 a vital source of vitamin B6. Lactase has no sequence similarity to its bacterial counterpart b galactosidase.…”
Section: The Mechanisms Causing Hypolactasia and Lactose Intolerancementioning
confidence: 99%
“…We assumed that the activity of cytosolic PNG hydrolase is physiologically relevant in releasing pyridoxine from the fraction of dietary PNG taken up by enterocytes without prior hydrolysis. We have shown that purified LPH of the brush-border membrane also catalyses PNG hydrolysis [12]. This indicates that PNG is a secondary substrate for LPH and that either partial hydrolysis of dietary PNG in the mammalian small intestine can occur at the brush-border membrane prior to absorption or PNG can be absorbed in intact form and hydrolysed by cytosolic PNGH.…”
Section: Introductionmentioning
confidence: 91%